Grammar translation method a necessary approach in foreign language learning - Cristales Cruz, Silvia Elena; Jovel Méndez, Mirna Carolina; López Solano, Luis David; Parada Rivera, Alba Estela; Yang Chen, Tai Yuan (2024)
The interest in facilitating the learning of a foreign language is not new, throughout the time, different approaches and techniques have been created and applied according to different contexts, learners’ needs, and their learning capacities, with the purpose that the language acquisition process is not inhibited but strengthened. Modern methodologies are focused on communicative aspects of the language and they are designed based on the socio-cultural aspects and educational contexts from developed countries. Also, these methodologies often require a high level of analysis from students. Therefore, when they are applied under a different context where learners possess diverse educational backgrounds and different levels of analytical reasoning, the teaching-learning process is hindered. In accordance to some official resources, this paper points out the difficulties of analysis that Salvadoran students present when they learn English with modern communicative methodologies. Also, some of the possible causes for the issue are examined. In addition, students’ reasons toward their English learning are described. Considering these facts, the Grammar Translation Method and its techniques are discussed. Also, the importance and benefits of those techniques are taken into account in order to state a better way to help Salvadoran students to cope with the analytical capability problem and to learn English more effectively. The novelty of the proposal asserted in this essay consists of a new way to approach this old, but not totally exhausted method by stating an adequate range of application of its techniques concurrently with the modern Communicative Approach. The description and analysis of different techniques of the Grammar Translation Method provide the readers with information regarding to this method. At the same time, emphasizing the importance and benefits these techniques provide. Furthermore, the useful techniques and the range of their application are determined by taking into account the present educational environment and the type of students involved in the process. In addition, this paper is addressed to educators involved in the English language teaching into the Salvadoran context. With the proper application of Grammar Translation techniques along with current communicative approaches in their teaching, better outcomes on students’ learning are expected.